Experimental investigations of flow over NACA airfoils 0021 and 4412 of wind turbine blades with and without Tubercles. Issue 1 (February 2022) - Butt, Usman; Hussain, Shafqat; Schacht, Stephan; Ritschel, Uwe
Experimental investigations of wind turbine blades having NACA airfoils 0021 and 4412 with and without tubercles on the leading edge have been performed in a wind tunnel. It was found that the lift coefficient of the airfoil 0021 with tubercles was higher at Re = 1.2×10 5 and 1.69×10 5 in post critical region (at higher angle of attach) than airfoils without tubercles but this difference relatively diminished at higher Reynolds numbers and beyond indicating that there is no effect on the lift coefficients of airfoils with tubercles at higher Reynolds numbers whereas drag coefficient remains unchanged. It is noted that at Re = 1.69×105, the lift coefficient of airfoil without tubercles drops from 0.96 to 0.42 as the angle of attack increases from 15° to 20° which is about 56% and the corresponding values of lift coefficient for airfoil with tubercles are 0.86 and 0.7 at respective angles with18% drop.